(3JaSjQ GdbQBf GdcQjes - (3fUQ Hf eMeO Hf CMeO Hf EHQGgje GdSeQbfOj GdMfaj ,CHh GddjK,J (B373 (3g` s ((3ChdjG Hf fhQG GdOjf GdQhei GdOhdhi s)
(3ChdgG (B:s
(3ShQI eQje cdgG ecHI JSYhf hKeGf BjGJ bGd QShd Gddg Udi Gddg Ydjg hSde ef bQCgG CYWi ef GdCLQ YTQ MSfGJ s
(3BNQgG (B:s
(3ShQI GdfGS eOfjI SJI BjGJ hQhi Yf YKeGf Hf hGbO bGd (B: (3aCQSfdi CHj Edi eMeO Hf GdefcOi CSGdg Yf GdeYhPJjf CgeG ef cJGH Gddg JYGdi ? bGd ef de jRYe CfgeG ef cJGH Gddg JYGdi aYdjg dYfg Gddg hGdedGFcI hGdfGS CLeYjf Je HMSf Gdgd hJhajbg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B348 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B91 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B490s
Keywords: (3GdJaSjQ hYdhe GdbQBfs